Assessment of the 2009 fertilizer voucher program in Kano and Taraba, Nigeria - Liverpool-Tasie, Lenis Saweda; Banful, Afua Branoah; Olaniyan, Babatunde (International Food Policy Research Institute, 2010)
This study analyzes the application of an input voucher program implemented in 2009 in two Nigerian states, Kano and Taraba. Using primary data collected from 1000 households, we explore the effect of the voucher program on the quantity and quality of fertilizer received, the timeliness of receipt, and the price paid by respondents. The findings indicate that program participants in both states were more formally educated than non participants, purchased fertilizer in groups, and had previously used subsidized fertilizer. Voucher program participants in our sample were more likely to receive subsidized fertilizer and in fact received 2.5 (Kano) and 3.5 (Taraba) more bags of subsidized fertilizer than non participants. They paid less than the market price but higher than was paid for subsidized fertilizer from other sources outside the program. Program participants in Taraba received their fertilizer late, and were more likely to be unsatisfied regarding unwanted substances found in their subsidized fertilizer. In Kano, there was no significant correlation found among participants in the study and the likelihood that they would either receive their fertilizer late, be unhappy about the quantity of the fertilizer received, or angry about the presence of unwanted substances in their fertilizer.